A Cross-Case Study Of The Competitive Advantage Of Private Higher Educational Institutions In Kuching, Sarawak - Lindong, Lambat Anak (2007)
This study examined the competitive advantage of private higher educational institutions (PHEIs) in Kuching, Sarawak. The primary focus of the study was on how PHEIs analyze and manage their external and internal environments and exploit their internal resources in order to position their institution to gain competitive advantage. The study also examined the distinctive competencies of PHEIs. It examined how the PHEIs exploit their distinctive competencies to gain and sustain competitive advantage in order to achieve market success in the higher education industry. Seven research questions were formulated to guide the study. The research was carried out through a case study of four PHEIs in the city of Kuching. The mostly qualitative data were gathered through semi-structured interviews with key informants, documents analysis and observations. The research findings revealed that: the management of PHEIs are not deliberate and systematic in their strategic planning, basing their decision more on intuition, although they do take stock of the external and internal factors affecting their institution. The five competitive forces espoused by Porter (1980) were found to be applicable in the study and depending on their strength, these forces do influence the competitiveness of PHEIs. In addition, the PHEIs do try to exploit their internal resources to deal with the competitive forces and make their institutions more competitive. The study also discovered that in order to be more competitive, the PHEIs adopted the differentiation focus strategy in their early years of establishment, after which there were attempts to switch to the differentiation strategy. It was also revealed that the distinctive competencies of PHEIs which could confer on them competitive advantage were mostly temporary and hence, the competitive advantage accrued was not sustainable. Finally, the market success of PHEIs was defined and the success of each PHEI was measured against a number of indicators. Overall, it was discovered that the PHEIs in the study were struggling to make ends meet. The implications of the findings are discussed and recommendations made to the PHEIs and higher education policy-makers to improve the competitiveness of PHEIs and to make them providers of quality higher education; and to researchers on the directions of related future research.